2011
DOI: 10.1159/000331333
|View full text |Cite
|
Sign up to set email alerts
|

<i>CDKL5</i>-Related Disorders: From Clinical Description to Molecular Genetics

Abstract: Mutations in the cyclin-dependent kinase-like 5 gene (CDKL5) have been described in girls with Rett-like features and early-onset epileptic encephalopathy including infantile spasms. To date, with more than 80 reported cases, the phenotype of CDKL5-related encephalopathy is better defined. The main features consist of early-onset seizures starting before 5 months of age, severe mental retardation with absent speech and Rett-like features such as hand stereotypies and deceleration of head growth. On the other h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
101
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(118 citation statements)
references
References 98 publications
5
101
0
6
Order By: Relevance
“…Cdkl5 -/y mice display hyperactivity, motor defects, reduced anxiety, decreased sociability, and impaired learning and memory. These phenotypes have been described in other ASD and RTT mouse models (2, 16, 17, 19, 26) and may mimic the absence of hand skills, intellectual disability, hyperactivity, and poor response to social interactions that have been described in CDKL5 patients (12,41). While video-EEG monitoring revealed an absence of spontaneous seizures in Cdkl5 -/y mice, ERP analysis showed attenuated and delayed ERP polarity peaks suggestive of impaired neuronal connectivity, which is consistent with findings in ASD and RTT patients (30,31) and animal models (19,28,29).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Cdkl5 -/y mice display hyperactivity, motor defects, reduced anxiety, decreased sociability, and impaired learning and memory. These phenotypes have been described in other ASD and RTT mouse models (2, 16, 17, 19, 26) and may mimic the absence of hand skills, intellectual disability, hyperactivity, and poor response to social interactions that have been described in CDKL5 patients (12,41). While video-EEG monitoring revealed an absence of spontaneous seizures in Cdkl5 -/y mice, ERP analysis showed attenuated and delayed ERP polarity peaks suggestive of impaired neuronal connectivity, which is consistent with findings in ASD and RTT patients (30,31) and animal models (19,28,29).…”
Section: Discussionmentioning
confidence: 70%
“…The limited understanding of CDKL5 function and its associated signal transduction pathways has hindered the development of therapeutics for CDKL5-related disorders. Current treatments focus on managing symptoms and reducing seizure frequency, but have limited effectiveness (12).…”
mentioning
confidence: 99%
“…18,[39][40][41] The vast majority of genetic alterations in CDKL5 45 reported a CDKL5 alteration in a 47,XXY boy with the early-onset seizure variant of Rett syndrome and concluded that a random pattern of XCI did not influence the severity of the disease. Skewed XCI has been proposed to explain the observed phenotypic variability in some females heterozygous for a mutated or deleted CDKL5 allele.…”
Section: Discussionmentioning
confidence: 99%
“…1 To date, with 480 reported cases, the phenotype of CDKL5-related encephalopathy is better defined. The main features consist of early-onset seizures starting before 5 months of age, severe mental retardation with absent speech, and Rett-like features such as hand stereotypies and deceleration of head growth.…”
Section: Introductionmentioning
confidence: 99%